Moving exercise research in multiple sclerosis forward (the MoXFo initiative): Developing consensus statements for research. (October 2020) - Dalgas, Ulrik; Hvid, Lars G; Kwakkel, Gert; Motl, Robert W; de Groot, Vincent; Feys, Peter; Op't Eijnde, Bert; Coote, Susan; Beckerman, Heleen; Pfeifer, Klaus; Streber, René; Peters, Stefan; et al.
Exercise as a subset of physical activity is a cornerstone in the management of multiple sclerosis (MS) based on its pleotropic effects. There is an exponential increase in the quantity of research on exercise in MS, yet a number of barriers associated with study content and quality hamper rapid progress in the field. To address these barriers and accelerate discovery, a new international partnership of MS-related experts in exercise has emerged with the goal of advancing the research agenda. As a first step, the expert panel met in May 2018 and identified the most urgent areas for moving the field forward, and discussed the framework for such a process. This led to identification of five themes, namely "Definitions and terminology, " "Study methodology, " "Reporting and outcomes, " "Adherence to exercise, " and "Mechanisms of action." Based on the identified themes, five expert groups have been formed, that will further (a) outline the challenges per theme and (b) provide recommendations for moving forward. We aim to involve and collaborate with people with MS/MS organizations (e.g. Multiple Sclerosis International Federation (MSIF) and European Multiple Sclerosis Platform (EMSP)) in all of these five themes. The generation of this thematic framework with multi-expert perspectives can bolster the quality and scope of exercise studies in MS that may ultimately improve the daily lives of people with MS.